Dipole Moment‐ and Molecular Orbital‐Engineered Phosphine Oxide‐Free Host Materials for Efficient and Stable Blue Thermally Activated Delayed Fluorescence. Issue 3 (21st November 2021) - Ihn, Soo‐Ghang; Jeong, Daun; Kwon, Eun Suk; Kim, Sangmo; Chung, Yeon Sook; Sim, Myungsun; Chwae, Jun; Koishikawa, Yasushi; Jeon, Soon Ok; Kim, Jong Soo; Kim, Joonghyuk; Nam, Sungho; et al.
Abstract: To utilize thermally activated delayed fluorescence (TADF) technology for future displays, it is necessary to develop host materials which harness the full potential of blue TADF emitters. However, no publication has reported such hosts yet. Although the most popular host for blue TADF, bis[2‐(diphenylphosphino)phenyl]ether oxide (DPEPO) guarantees high‐maximum external quantum efficiency (EQEmax ) TADF devices, they exhibit very short operational lifetimes. In contrast, long‐lifespan blue TADF devices employing stable hosts such as 3′, 5‐di(9H‐carbazol‐9‐yl)‐[1, 1′‐biphenyl]‐3‐carbonitrile (mCBP‐CN) exhibit much lower EQEmax than the DPEPO‐employed devices. Here, an elaborative approach for designing host molecules is suggested to achieve simultaneously stable and efficient blue TADF devices. The approach is based on engineering the molecular geometry, ground‐ and excited‐state dipole moments of host molecules. The engineered hosts significantly enhance delayed fluorescence quantum yields of TADF emitters, as stabilizing the charge‐transfer excited states of the TADF emitters and suppressing exciton quenching, and improve the charge balance. Moreover, they exhibit both photochemical and electrochemical stabilities. The best device employing one of the engineered hosts exhibits 79% increase in EQEmax compared to the mCBP‐CN‐employed device, together with 140% and 92‐fold increases in operational lifetime compared to the respective mCBP‐CN‐ and the DPEPO‐based devices. Abstract : By using dipole moment‐ and molecular orbital‐engineered host materials which are phosphine oxide‐free, high efficiency and long lifespan can be simultaneously achieved from the organic light‐emitting diodes based on a donor‐acceptor type thermally activated delayed fluorescent emitter.